Spectrumize: Spectrum-efficient Satellite Networks for the Internet of Things - Singh, Vaibhav; Chakraborty, Tusher; Jog, Suraj; Chabra, Om, Deepak Vasisht; Chandra, Ranveer (USENIX NSDI, 2024)
Low Earth Orbit satellite constellations are gaining traction for providing connectivity to low-power outdoor Internet of Things (IoT) devices. This is made possible by the development of low-cost, low-complexity pico-satellites that can be easily launched and deployed, offering global connectivity without the need for Earth-based gateways. In this paper, we report the space-to-Earth communication bottlenecks derived from our experience of deploying an IoT-focused pico-satellite. Specifically, we characterize the challenges posed by the low link budgets, satellite motion, and packet collisions. To address these challenges, we design a new class of technique that use the Doppler shift caused by the satellite's motion as a unique signature for packet detection and decoding, even at low signal-to-noise ratios and in the presence of collisions. We integrate these techniques into our system, called Spectrumize, and evaluate its performance through both simulations and real-world deployments. Our evaluation shows that Spectrumize performs 3x better compared to classic approach in detecting packet with over 80% average accuracy in decoding.